Clinical and molecular characterization of adult patients with late‐onset MTHFR deficiency. Issue 3 (2nd November 2020) - Marelli, Cecilia; Lavigne, Christian; Stepien, Karolina M.; Janssen, Mirian C. H.; Feillet, Francois; Kožich, Viktor; Jesina, Pavel; Schule, Rebecca; Kessler, Christoph; Redonnet‐Vernhet, Isabelle; Regnier, Adeline; Burda, Patricie; et al.
Abstract: 5, 10‐Methylenetetrahydrofolate reductase (MTHFR) deficiency usually presents as a severe neonatal disease. This study aimed to characterize natural history, biological and molecular data, and response to treatment of patients with late‐onset MTHFR deficiency. The patients were identified through the European Network and Registry for Homocystinuria and Methylation Defects and the Adult group of the French Society for Inherited Metabolic Diseases; data were retrospectively colleted. To identify juvenile to adult‐onset forms of the disease, we included patients with a diagnosis established after the age of 10 years. We included 14 patients (median age at diagnosis: 32 years; range: 11‐54). At onset (median age: 20 years; range 9‐38), they presented with walking difficulties (n = 8), cognitive decline (n = 3) and/or seizures (n = 3), sometimes associated with mild mental retardation (n = 6). During the disease course, symptoms were almost exclusively neurological with cognitive dysfunction (93%), gait disorders (86%), epilepsy (71%), psychiatric symptoms (57%), polyneuropathy (43%), and visual deficit (43%). Mean diagnostic delay was 14 years. Vascular events were observed in 28% and obesity in 36% of the patients. One patient remained asymptomatic at the age of 55 years. Upon treatment, median total homocysteine decreased (from 183 μmol/L, range 69‐266, to 90 μmol/L, range 20‐142) and symptoms improved (n = 9) or stabilized (n = 4). Missense pathogenic variants in the C‐terminal regulatory domain of the protein were over‐represented compared to early‐onset cases. Residual MTHFR enzymatic activity in skin fibroblasts (n = 4) was rather high (17%‐58%). This series of patients with late‐onset MTHFR deficiency underlines the still unmet need of a prompt diagnosis of this treatable disease.